Should teachers use L1 in EFL classroom? - Mahmud, Shahnaz (Journal of NELTA, 2018)
English language teachers customarily rule out the use of mother tongue for teaching English. Reflecting on the theoretical underpinnings and empirical research on the use of mother tongue (L1) in English classroom and its ongoing debate the present study aims to explore teachers’ and students’ perceptions of it. A mixed method approach using questionnaire and interview is employed to analyze Bangladeshi university teachers’ and students’ belief and perceptions of teaching English with the help of L1. The study also attempts to discuss the strengths and weaknesses of using L1. Results indicate that both teachers and students perceive the necessity of judicious use of L1 to facilitate learning and acquisition of English as a foreign language (EFL).